Double Six Tragedy and Implications of Political Development in Sabah, Malaysia - Aziz, Hamdan (SOSIOHUMANIKA, 2013)
ABSTRACT: On June 6, 1976, Malaysians were shocked by a plane crash killing the top ranks leaders of the newly appointed state government of Sabah, Malaysia. The Australian-made aircraft types NOMAD plane crashed in the village of Sembulan Baru, which is located two miles away from the International Airport and the city of Kota Kinabalu. âDouble Sixâ tragedy on June 6, 1976 in Sabah, Malaysia has resulted in widespread dissemination of conspiracy theory. This crash killed all the people on board, including Tun Mohd Fuad Stephens, who has been shortly appointed as the Chief Minister of Sabah. The sudden death of Tun Mohd Fuad Stephens created opportunity for Datuk Mohd Harris Salleh to be appointed as the Chief Minister of Sabah. This paper seeks and analyses the causes behind the crash which remain unknown. This paper applies also the historical method analysis, comprising an analysis of the most pertinent documents. In addition, this paper presents the views of high profile individual such as Datuk Mohd Harris Salleh and Toh Puan Hajjah Rahimah Stephens how events can occur. However, writer strongly agree with Datuk Harris Salleh and Toh Puan Hajjah Rahimah Stephens that âhuman errorâ was a major factor of âDouble Sixâ tragedy.KEY WORD: Double six tragedy, crash, Chief Ministers of Sabah, human erros, technical erros, and conspiracy theory.Â RESUME: Kertas kerja ini bertajuk âTragedi Double Six dan Implikasi terhadap Perkembangan Politik di Sabah, Malaysiaâ. Pada 6 Jun 1976, rakyat Malaysia telah dikejutkan oleh nahas sebuah pesawat udara yangÂ mengorbankan seorang pemimpin kerajaan Sabah yang baru dilantik. Pesawat udara jenis NOMAD buatan Australia telah jatuh di Kampong SembulanÂ Baru, dua batu jauhnya dari Lapangan Terbang Antarabangsa dan Kota Kinabalu. Berlakunya peristiwa âDouble Sixâ pada 6 Jun 1976 di Sabah, Malaysia telah mengundang pelbagai penafsiran terhadap punca-punca nahas. Peristiwa ini menyebabkan semua anak kapal terbunuh, termasuk Tun Mohd Fuad Stephens yang ketika itu menjawat jawatan Ketua Menteri Sabah. Kematian Tun Mohd Fuad Stephens telah memberi peluang kepada Datuk Mohd Harris Salleh apabila beliau dilantik sebagai Ketua Menteri Sabah. Kertas kerja ini berusaha mengenal pasti faktor-faktor berlakunya nahas dengan menggunakan pendekatan sejarah serta bergantung sepenuhnya kepada analisis dokumen. Selain itu, kertas kerja ini juga mengemukakan pandangan beberapa orang tokoh seperti Datuk Harris Salleh dan Toh Puan Hajjah Rahimah Stephens bagaimana galuran peristiwa boleh berlaku. Walau bagaimanapun, penulis bersetuju sangat dengan pandangan Datuk Mohd Harris Salleh and Toh Puan Hajjah Rahimah Stephens bahawa âkesilapan manusiaâ adalah punca utama nahas dalam tragedi âDouble Sixâ. KATA KUNCI: Tragedi double six, nahas, Ketua-ketua Menteri Sabah, kesilapan manusia, kerosakan teknikal, dan teori konspirasi.About the Author: Dr. Hamdan Aziz is currently a Senior Lecturer at the Department of Nationhood and Civilization Studies UMT (Malaysia University of Terengganu). He can be contacted via e-mail at: hamdan.aziz@umt.edu.my and naqiudin@yahoo.comHow to cite this article? Aziz, Hamdan. (2013). âDouble Six Tragedy and Implications of Political Development in Sabah, Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.1 [Mei], pp.89-96. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 27, 2013); Revised (April 29, 2013); and Published (May 20, 2013). Â  Â